2014
DOI: 10.1016/j.gaceta.2014.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Determinantes del uso de distintos niveles asistenciales en el Sistema General de Seguridad Social en Salud y Sistema Único de Salud en Colombia y Brasil

Abstract: In both countries, the influence of the determinants of use differed according to the level of care used, emphasizing the need to analyze healthcare use by disaggregating it by level of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
0
12

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 23 publications
3
25
0
12
Order By: Relevance
“…In general, the states with the highest ESF coverage had a reduction in ICSAPs of around 5% over five years. 15 The same phenomenon was observed in this study for Mato Grosso do Sul where there was a reduction of ICSAPs with the expansion of the ESF, considered to be high for all clusters, except cluster 4, which has a coverage classified as average.…”
supporting
confidence: 84%
“…In general, the states with the highest ESF coverage had a reduction in ICSAPs of around 5% over five years. 15 The same phenomenon was observed in this study for Mato Grosso do Sul where there was a reduction of ICSAPs with the expansion of the ESF, considered to be high for all clusters, except cluster 4, which has a coverage classified as average.…”
supporting
confidence: 84%
“…Authors have published these studies between 1999 and 2017 (median: 2009) 5,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37 (Table 1). The authors of five studies reported having no conflicts of interest 19,28,31,33,35 , while in the other studies the authors did not disclose whether they had any conflicts of interest, nor did they examine interviewers' biases (in qualitative studies).…”
Section: Resultsmentioning
confidence: 99%
“…Por otro lado, el tener algún problema de salud crónico, se asoció a una menor prevalencia de NUSFPS (Tabla 3). (5,6) . En Europa, la prevalencia de NUSFPS bucal en España, Suecia y Dinamarca osciló entre 65,7 y 20%, respectivamente (7,8) .…”
Section: Modelos Lineales Generalizados: Crudos Y Ajustadosunclassified
“…Asimismo, el INEI reportó la prevalencia de utilización de los servicios de salud por haber padecido de algún problema de salud crónico y no crónico desde el año 2004, las cuales fueron de 38,0 y 38,7%, respectivamente; este porcentaje se ha incrementado de forma progresiva hasta que en el año 2015 alcanzó porcentajes de 41,3 y 53,5%, correspondientemente (10) . Se halló una mayor prevalencia de NUSFPS en aquellos participantes de sexo masculino, lo cual concuerda con lo hallado en estudios realizados en Colombia, Brasil y Dinamarca (5,11,12) . Creemos que esta situación podría deberse al carácter predominantemente machista presente en la población peruana (13) ; el varón tiende a trabajar durante largas jornadas, con reducido tiempo para el cuidado de su salud.…”
Section: Modelos Lineales Generalizados: Crudos Y Ajustadosunclassified
See 1 more Smart Citation